Analisis Kearifan Lokal Keripik Sanjai Di Kota Bukittinggi Sebagai Sumber Belajar Biologi Materi Keanekaragaman Hayati - Kurnia Wulansari; Dian Intan Rahmadhani; Nur Aisyah Putri; Sri Wahyuni; Abdul Razak; Fitri Arsih (Institut Agama Islam Negeri Kerinci, 2022)
Indonesia has a variety of cultures and customs that are spread throughout the region so that it has its own local wisdom. Local wisdom is knowledge gained from previous experience based on the surrounding environment that can be used to solve problems and fulfill daily needs. One form of local wisdom in Bukittinggi City is Sanjai Chips with raw material, namely cassava. By utilizing cassava, it can be implemented in biology learning, namely about material on biodiversity. This study aims to analyze the local wisdom of sanjai chips in biology learning. This type of research is descriptive research using the observation method. Based on the results of the study showed that the raw material for sanjai chips used was yam lambao or sweet potato bread, with a harvest age of about 6-7 months. local wisdom Sanjai chips have local wisdom (indigenous science) which contains the concept of Biology so that teachers are expected to be able to use the local cultural context in the Biology learning process.